Time Estimation Among Low‐Functioning Individuals With Autism Spectrum Disorders: Evidence of Poor Sensitivity to Variability of Short Durations. Issue 2 (26th February 2014) - Brodeur, Darlene A.; Gordon Green, Cathryn; Flores, Heidi; Burack, Jacob A.
<x xml:space="preserve">Abstract</x> Time estimation of short durations (under 1 sec) was examined in low‐functioning individuals with autism spectrum disorder (ASD) and typically developing (TD) children matched on mental age. Temporal bisection and generalization tasks were used to examine basic perceptual timing mechanisms. For both tasks, the participants with ASD demonstrated less sensitivity to variability in short durations than the TD children, adding to a growing body of literature suggesting deficits in timing exist for longer durations. The results highlight the need to examine multiple levels of processing of time‐related information from basic perceptual mechanisms to higher level cognitive mechanisms. Autism Res 2014, 7: 237–244. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.